The sequence analysis of M2 gene for identification of amantadine resistance in avian influenza virus (H9N2 subtype), detected from broiler chickens with respiratory syndrome during 2016-2018, in Isfahan-Iran - Majid Gholami-Ahangaran; Asal Basiratpour; Oveys Pourmahdi; Pedram Khorrami; Mehrdad Ostadpoor; Mohammad Javad Mirbagheri; Asiye Ahmadi-Dastgerdi (Acta Scientiarum. Animal Sciences, 2022)
Amantadine and rimantadine are used for prevention and treatment of influenza A virus (IAV) infection. The rates of resistant IAVs have been increasing globally. However, amino acid substitutions in the M2 transmembrane channel lead to amantadine resistance. The residues of 26, 27, 30, 31 or 34 are marker of amantadine resistance in IAVs. In this study, 15 pooled tracheal samples collected from 15 chicken farms with severe respiratory sign and mortality in 2016-2018. After identification of influenza A and H9 subtype, the 1027 bp fragment of M gene was sequenced for molecular evaluation of amantadine resistance in AIV strains. Results showed 12 out of 15 pooled samples were positive for IAV and H9 subtype. Based on M2 gene analysis, 8 out of 12 (66.66%) were resistance to amantadine. Four out of 8 (50%) showed S31N substitution (serine to asparagine) and four out of 8 (50%) have V27A substitution (valine to alanine). There was no dual amantadine resistance mutation in any specimens. In conclusion, the emergence of amantadine resistance variants of AIV in Iran, can raise concerns about controlling of the seasonal and the future pandemic influenza. Therefore, greater caution is needed in the use of adamantanes